Applying a novel environmental health framework theory (I-ACT) to noise pollution policies in the United States, United Kingdom, and the Netherlands. Issue 12 (15th October 2018) - Hammer, Monica S.; Fan, Yi; Hammer, Suzanne S.; Swinburn, Tracy K.; Weber, Miriam; Weinhold, Diana; Neitzel, Richard L.
Abstract : I-ACT is a theoretical framework designed to guide environmental health improvement efforts. I-ACT identifies four interacting drivers of change that influence an environmental health aim: (1) Information systems; (2) public Awareness; (3) leadership and Coordination; and, (4) Tools. Actors can use I-ACT to clarify roles and identify strategies to impact their aim. Here, we apply the I-ACT framework to a ubiquitous environmental hazard, noise pollution, comparing three Western countries: the United States, the Netherlands, and the United Kingdom. Our approach statutorily defines each country's designated aims, qualitatively evaluates its information systems, awareness, coordination, and tools, and assesses the role of these drivers in achieving the aims. While the Netherlands and the United Kingdom demonstrated robust activity for some drivers, the United States showed limited activity and achievement. There appeared to be an association between achievement of aims and demonstrated elements of each driver, providing support for the utility of I-ACT.